2020
DOI: 10.1186/s13045-020-00870-w
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib dose modifications in the management of CLL

Abstract: Background: Ibrutinib is a Bruton tyrosine kinase inhibitor approved for the treatment of chronic lymphocytic leukemia (CLL) in 2014. Ibrutinib is often used to treat patients who are younger than the patients originally included in theclinical trials have additional unfavorable prognostic factors and suffer from additional comorbidities excluded from the original phase III trials. Our objective was to examine current clinical practices and their impact in this expanded population of CLL patients who often req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 30 publications
4
24
1
Order By: Relevance
“…Novel agents, including inhibitors of B-cell receptor signaling pathway (ibrutinib, acalabrutinib, idelalisib and duvelisib) and the inhibitor of the antiapoptotic protein BCL-2 (venetoclax), are superior compared to conventional chemoimmunotherapy (CIT) regimens. Cellular immunotherapy with chimeric antigen receptor T-cell (CAR-T) and allogeneic stem cell transplant (allo-SCT) are available for high-risk patients [3][4][5][6][7][8][9]. New challenges emerge when patients relapse on novel agents, and optimal sequencing strategies have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Novel agents, including inhibitors of B-cell receptor signaling pathway (ibrutinib, acalabrutinib, idelalisib and duvelisib) and the inhibitor of the antiapoptotic protein BCL-2 (venetoclax), are superior compared to conventional chemoimmunotherapy (CIT) regimens. Cellular immunotherapy with chimeric antigen receptor T-cell (CAR-T) and allogeneic stem cell transplant (allo-SCT) are available for high-risk patients [3][4][5][6][7][8][9]. New challenges emerge when patients relapse on novel agents, and optimal sequencing strategies have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…While ibrutinib is generally well-tolerated, treatment discontinuations or interruptions due to toxicity may limit the efficacy of ibrutinib in patients receiving continuous oral therapy. A recent review reported that discontinuation rates for ibrutinib were similar between clinical trials and real-world practice (32% vs 34%, respectively), though the reasons for discontinuation differed [ 33 ]. One large-scale, real-world study reported that 41% of patients discontinued ibrutinib and that ibrutinib toxicity was the main reason for these discontinuations [ 34 ].…”
Section: Current Treatment Strategiesmentioning
confidence: 99%
“…Real‐world data show that intolerance is the most frequent reason for discontinuation or interruption of ibrutinib 41,54,55 . Dose reductions and temporary breaks are common and often required 41,55,56 .…”
Section: Fixed‐duration or Continuous Therapy For Treatment‐naïve Cllmentioning
confidence: 99%
“…Younger, fit patients may have a lower incidence of discontinuation or interruption due to AEs, as observed in E1912 12,40 . Strategies to minimize ibrutinib intolerance and maximize efficacy are needed 41,54,56 …”
Section: Fixed‐duration or Continuous Therapy For Treatment‐naïve Cllmentioning
confidence: 99%